Neodvisna osebna zavarovanja v slovenskem pravu in DCFR - Pirc, Jure (Podjetje in delo, 2018)
The subject of this paper is a comparison of independent personal security in Slovenian law and the Draft Common Frame of Reference. European contract law already holds an important role in the law of the Community, which is only expected to intensify over time. DCFR is part of that process and the first attempt of comprehensive examination of primarily the law of obligation, where contracts that are traditionally subject to autonomous regulation are not excluded. A first demand guarantee is one of these. In DCFR, it is regulated with other independent personal securities, whereas in the Obligations Act, it is a special contract. This paper presents the differences, as well as the similarities, between the regulation of independent personal security in Slovenian law and DCFR, by individual elements. For each of these elements, a precise analysis of rights and obligations of subjects is presented.
Keywords: bančna garancija na prvi poziv; neodvisna bančna garancija; neodvisna osebna zavarovanja; osebna zavarovanja; skupni referenčni okvir; zavarovanje pogodbenih obveznosti